High Participant Satisfaction Achieved Using Cryolipolysis for Fat Reduction of the Abdomen and Flanks. (17th December 2021) - Tan, Terence; Snell, Broughton; Braun, Martin; Mohan, Sach; Jo, Esther; Patel, Vaishali; Zheng, Suzanne; Manson Brown, Stephanie; Hickling, Matthew
Abstract: Background: Patient-reported outcome (PRO) data evaluating the physical and psychosocial impact of cryolipolysis (CoolSculpting) treatment are limited. Objectives: The aim of this study was to assess, by means of PRO instruments, multidimensional aspects of satisfaction following cryolipolysis treatment of the flanks and abdomen. Methods: This was a multinational, prospective, single-cohort, interventional study. The primary endpoint was the proportion of participants stating they were "satisfied" or "very satisfied" with treatment at 12 weeks post final treatment. Secondary endpoints included satisfaction categorized by treatment area, total number of treatment cycles, baseline BMI, and fat volume reduction measured by 3-dimensional photography at 12 weeks post final treatment. Exploratory endpoints assessed the physical and psychosocial impacts of treatment. Safety was monitored throughout the study. Results: Of 112 participants who were treated, 74.1% were female. The mean age and BMI were 42.5 years and 24.9 kg/mg 2, respectively. Of the 106 evaluable participants, 89.6% were "satisfied" or "very satisfied" with treatment results. Satisfaction was high regardless of body area(s), total number of treatment cycles, or baseline BMI. Mean [standard deviation] fat volume reduction was 264.8 [411.4] mL. Overall, 90.6% reported "noticeable" or "very noticeable" fat reduction, 89.6% were "likely" or "very likely" to treat additional areas, and 93.4% would recommend cryolipolysis to a friend. Twenty-four (21.4%) participants reported treatment-emergent adverse events; 23 (20.5%) reported these as adverse device effects. No serious device-related or unanticipated adverse effects occurred. Conclusions: Cryolipolysis (CoolSculpting) for fat reduction of the flanks and/or abdomen was well-tolerated and associated with high levels of satisfaction across multidimensional PROs. Level of Evidence: 4: